The Contribution of Classical Muslim Thinkers to the Development of Islamic Education: A Thematic Literature Review - Rahmawati Azizah (Samarinda International Journal of Islamic Studies (SIJIS), 2025)
This thematic literature review examines the significant contributions of classical Muslim thinkers to the evolution of Islamic education. The study employs a qualitative approach, analyzing key texts and scholarly works to identify the core principles and pedagogical approaches advocated by prominent figures such as Ibn Sina (Avicenna), Al-Ghazali, and Ibn Khaldun. The review synthesizes existing research to explore themes including curriculum development, the role of the teacher, the aims of education, and the integration of religious and secular knowledge. The findings reveal a rich tradition of educational thought that emphasized holistic development, critical thinking, and the cultivation of moral character. The review highlights the enduring relevance of classical Muslim educational philosophies for contemporary Islamic education, offering insights for educators and policymakers seeking to create effective and culturally relevant learning environments. This study underscores the importance of understanding the historical roots of Islamic education to address current challenges and foster intellectual growth within Muslim communities. Furthermore, it examines the interplay between religious and secular knowledge, the role of education in shaping individuals and societies, and the historical context that shaped the educational ideals of these thinkers. The review concludes by emphasizing the need for further research to explore the practical applications of these classical principles in modern educational settings.